2016
DOI: 10.1177/0733464815608492
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the Family Empowerment Scale With Custodial Grandmothers

Abstract: The Family Empowerment Scale (FES) was developed specifically to assess empowerment in families with emotional disorders. Its relevance to custodial grandfamilies is reflected in the difficulties in grandchildren's social, emotional, and behavioral functioning, wherein such difficulties may be explained via either reactions to changes in their family structure or in their responses to the newly formed family unit. Utilizing 27 items derived from the 34-item version of the FES, which had represented differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 59 publications
0
14
0
2
Order By: Relevance
“…Dále jsou hledány společné a rozdílné faktory spojené s psychologickým zdravím prarodičů žijících v domácnostech s vynechanou generací (Park 2009) a také vliv péče o vnouče na očekávanou délku života a blahobyt jak pečujících prarodičů, tak vnoučete (Worrall 2009;Gordon et al 2010;Arpino, Balbo, Bordone 2018). Součástí je i výzkum platnosti měřítka zplnomocnění rodin (FES), jeho vnitřní konzistence, konstrukce a výzkum struktury faktorů (Hayslip et al 2017).…”
Section: Zdraví Pečujících Prarodičůunclassified
See 1 more Smart Citation
“…Dále jsou hledány společné a rozdílné faktory spojené s psychologickým zdravím prarodičů žijících v domácnostech s vynechanou generací (Park 2009) a také vliv péče o vnouče na očekávanou délku života a blahobyt jak pečujících prarodičů, tak vnoučete (Worrall 2009;Gordon et al 2010;Arpino, Balbo, Bordone 2018). Součástí je i výzkum platnosti měřítka zplnomocnění rodin (FES), jeho vnitřní konzistence, konstrukce a výzkum struktury faktorů (Hayslip et al 2017).…”
Section: Zdraví Pečujících Prarodičůunclassified
“…Rodičovská soběstačnost, znalost podpůrných služeb a jejich využívání je důležitým faktorem pro zvládnutí prarodičovské péče o dítě (Hayslip et al 2017) a rovněž vztahové, kulturní, právní a sociálně-ekonomické otázky mají zásadní dopad na to, jak pečující prarodiče vnímají péči o vnouče (Worrall 2009). Také děti v prarodinách čelí mnohým potížím.…”
Section: Blahobyt Prarodinunclassified
“…I particularly liked how this article "re-purposed" a strong measure from a different context and illustrated its utility among grandparents caring for grandchildren. The final article in this issue shares some similarities with Miyawaki (2017) and Hayslip et al (2017) in its exploration of intergenerational relationships and culture. Boucher (2017) offers an in-depth qualitative analysis of Dominican and Puerto Rican elders' perspectives regarding end-of-life decisions.…”
Section: Journal Of Applied Gerontology 36(3)mentioning
confidence: 99%
“…This pattern of findings did not extend to their own expectations for future long-term care, which seemed to revolve around entry into typical/mainstream residential long-term care settings. Hayslip, Smith, Montoro-Rodriguez, Streider, and Merchant (2017) completed a rigorous analysis of the Family Empowerment Scale (FES) in the context of grandmothers serving as custodial parents to their grandchildren. Utilizing a large and diverse sample, Hayslip et al found that the 27-item version of the FES generated three domains that differed somewhat from the original FES.…”
Section: Journal Of Applied Gerontology 36(3)mentioning
confidence: 99%
“…Family empowerment is gaining importance, especially in situations that cause disability (2). Empowerment is an important concept for the status of parents within health care services (1) because family empowerment has been shown to have a positive effect on different patient populations in various cultures (1,(3)(4)(5) Researchers have used various approaches and measurement tools to assess family empowerment (6). In cases of psychiatric disorders, family caregiver empowerment is a significant factor in coping with the nature of the disease.…”
Section: Introductionmentioning
confidence: 99%